计算:(x+1)(x-2)(x-3)(x-6)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 22:23:47
计算:(x+1)(x-2)(x-3)(x-6)计算:(x+1)(x-2)(x-3)(x-6)计算:(x+1)(x-2)(x-3)(x-6)(x+1)(x-2)(x-3)(x-6)==(x+1)(x-6
计算:(x+1)(x-2)(x-3)(x-6)
计算:(x+1)(x-2)(x-3)(x-6)
计算:(x+1)(x-2)(x-3)(x-6)
(x+1)(x-2)(x-3)(x-6)=
=(x+1)(x-6)(x-2)(x-3)
=(x^2-5x-6)(x^2-5x+6)
=(x^2-5x)^2-36
=x^4-10x^3+25x^2-36
你是怎么读书的啊!!!
对阿,你怎么读书的阿
x^4-10x^3+25x^2-36
x^4-10x^3+25x^2-26
用(x+1)(x-6),(x-2)(x-3)
得(x^2-5x-6)(x^2-5x+6)
设x^2-5x=y
(y-6)(y+6)=y^2-36=(x^2-5x)^2-36=x^2(x-5)^2-36
=x^4-10x^3+25x^2-26
一步步算```
计算:x/(x-1)-(x+3)/(x^-1)*(x^2+2x+1)/(x+3)
计算:[(x^2 - 4)/(x^2 - x - 6) + (x+2)/(x-3)] / (x+1)/(x-3)
计算:1-2x+x^2/x-x^3*xy+x^2y/x-x^2
计算(x+1)(x+2)(x+3)(x+4)
计算:(x+1)(x-2)(x-3)(x-6)
计算 x(x+3)-(x-1)(x-2)
如何计算 (x+1)(x+2)(x+3)(x+4)
计算(X-1)(X-2)(X-3)(X-4)
(x-1)(x-2)(x-3)(x-4)-24计算
计算:x(x^2+x-1)-(x^2-x+1)
x/x-3-5x/x^2-x-6计算
计算:[(x+2)/(x+3) - (x+1)/(x+2) + (x+4)/(x+5) - (x+3)/(x+4) / (x^2 + 7x + 13)/(x^2 + 8x + 15)
计算:x/x-2 - 5x/x²-x-6计算:x/x-3 - 5x/x²-x-6
2x/x-1+1/x+3-3x+5/x^2+2x-3计算,
计算3x^3-(x^2 +2x)(3x-1)-3(x+5)(x-2)
计算 2+x+3/x-1*x^2-2x+1/x^2+6x+9
计算:(2x+3)(3x-4)>(x+1)(x-1)+5x(x+3)+7
计算,X(3x-2)(x+1)-2x(x-2)(x+2)